Aquaculture in Shared Waters: Lessons for Diverse and Inclusive Workforce Training - Johnson, Teresa; Veo, Jessica (Maine Policy Review, 2023)
In 2021, the Maine Aquaculture Road Map identified four broad goals as critical to sustainably strengthening Maine’s aquaculture sector over the next ten years, with diversity, equity, and inclusion (DEI) listed as being important. This commentary reflects on lessons learned from the Aquaculture in Shared Waters (AQSW) training program. We describe the program, share key accomplishments and challenges, and consider opportunities for enabling more inclusive and equitable entry into the aquaculture sector.